A classroom data literacy intervention for pre-service teachers. (August 2015) - Reeves, Todd D.; Honig, Sheryl L.
Abstract: This pretest-posttest study investigated 64 pre-service teachers' perceptions of the impact of a 6-h data literacy intervention, which involved scoring classroom assessments, and analyzing, interpreting, and making decisions based on the data. The study also examined changes in participants' self-reported attitudes and beliefs and objectively-measured data literacy during the intervention. Participant reports suggest that the intervention increased the pre-service teachers' knowledge and skills related to data literacy. Pretest-posttest changes were also observed in three attitudes/beliefs ( d s ranged from .34 to .46) and data literacy ( d  = .60). Findings contribute to the small and nascent body of scholarship concerning pre-service data literacy interventions. Highlights: Investigated 6-h classroom data literacy intervention for pre-service teachers. Intervention was facilitated, procedural, technology-enhanced, and collaborative. Gains observed in attitudinal/belief and objective data literacy measures. Participants reported positive intervention impacts on 23 data literacy facets. Qualitative data imply favorable perceptions around tool use and faculty coaching.